2018
DOI: 10.1182/bloodadvances.2018016501
|View full text |Cite
|
Sign up to set email alerts
|

MECOM-associated syndrome: a heterogeneous inherited bone marrow failure syndrome with amegakaryocytic thrombocytopenia

Abstract: Key Points Germ line mutations in MECOM cause a heterogeneous bone marrow failure syndrome with congenital hypomegakaryocytic thrombocytopenia. MECOM-associated syndrome includes various organ malformations with variable penetrance, including radioulnar synostosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
113
0
14

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(134 citation statements)
references
References 49 publications
2
113
0
14
Order By: Relevance
“…Expression of a second set of genes with strong connections to CAKUT -MECOM, PAPPA2, and TNFRSF11B -coincide in cluster 18 (Figure 5D). MECOM mutations were recently identified in patients with kidney malformations (Germeshausen et al, 2018), Pappa2 is connected to salt-induced hypertension in rats (Cowley et al, 2016), and TNFRSF11B, also known as Osteoprotegerin, is linked to hypertension and chronic kidney disease (Bernardi et al, 2017) and was confirmed to be strongly expressed in the macula densa and also more broadly in the distal tubule (Supplementary figure 8G, H).…”
Section: Beyond the Single Gene: Gene Network In Development And Dismentioning
confidence: 94%
“…Expression of a second set of genes with strong connections to CAKUT -MECOM, PAPPA2, and TNFRSF11B -coincide in cluster 18 (Figure 5D). MECOM mutations were recently identified in patients with kidney malformations (Germeshausen et al, 2018), Pappa2 is connected to salt-induced hypertension in rats (Cowley et al, 2016), and TNFRSF11B, also known as Osteoprotegerin, is linked to hypertension and chronic kidney disease (Bernardi et al, 2017) and was confirmed to be strongly expressed in the macula densa and also more broadly in the distal tubule (Supplementary figure 8G, H).…”
Section: Beyond the Single Gene: Gene Network In Development And Dismentioning
confidence: 94%
“…1). [34][35][36] The Genotyping and Phenotyping of Platelets Project (GAPP) demonstrated the efficiency of combining platelet phenotyping and WES for elucidating pathogenic-genetic variants that give rise to ITs with secondary qualitative platelet defects. Originally, investigators examined up to 329 genes and identified candidate defects in patients with G i -coupled protein signaling and adenosine triphosphate (ATP) secretion abnormalities.…”
Section: Whole-genome Sequencingmentioning
confidence: 99%
“…25 Highly consistent with mouse studies, heterozygous loss-offunction mutations or deletions of the MECOM gene have been identified in radioulnar synostosis with amegakaryocytic thrombocytopenia patients. [26][27][28] The patients suffer from amegakaryocytic thrombocytopenia followed by BM failure, as well as other symptoms, including radioulnar synostosis, clinodactyly, cardiac and renal malformations, B cell deficiency, and presenile hearing loss.…”
Section: Mecom (Mds1 and Evi1 Complex Locus)mentioning
confidence: 99%